Ginsenoside 20(S)-protopanaxadiol induces cell death in human endometrial cancer cells via apoptosis - Jo, Hantae; Jang, Dongmin; Park, Sun Kyu; Lee, Mi Gi; Cha, Byungsun; Park, Chaewon; Shin, Yong Sub; Park, Hyein; Baek, Jin myoung; Heo, Hyojin; Brito, Sofia; Hwan, Hyun Gyu; et al. (Journal of Ginseng Research, 2021)
Background: 20(S)-protopanaxadiol (20(S)-PPD), one of the aglycone derivatives of major ginsenosides, has been shown to have an anticancer activity toward a variety of cancers. This study was initiated with an attempt to evaluate its anti-cancer activity toward human endometrial cancer by cell and xenograft mouse models. Methods: Human endometrial cancer (HEC)-1A cells were incubated with different 20(S)-PPD concentrations. 20(S)-PPD cytotoxicity was evaluated using MTT assay. Apoptosis was detected using the annexin V binding assay and cell cycle analysis. Cleaved poly (ADP-ribose) polymerase (PARP) and activated caspase-9 were assessed using western blotting. HEC-1A cell tumor xenografts in athymic mice were generated by inoculating HEC-1A cells into the flank of BALB/c female mice and explored to validate 20(S)-PPD anti-endometrial cancer toxicity. Results: 20(S)-PPD inhibited HEC-1A cell proliferation in a dose-dependent manner with an IC50 value of 3.5 μM at 24 h. HEC-1A cells morphologically changed after 20(S)-PPD treatment, bearing resemblance to Taxol-treated cells. Annexin V-positive cell percentages were 0%, 10.8%, and 58.1% in HEC-1A cells when treated with 0, 2.5, and 5 μM of 20(S)-PPD, respectively, for 24 h. 20(S)-PPD subcutaneously injected into the HEC-1A cell xenograft-bearing mice three times a week for 17 days manifested tumor growth inhibition by as much as 18% at a dose of 80 mg/kg, which sharply contrasted to controls that showed an approximately 2.4-fold tumor volume increase. These events paralleled caspase-9 activation and PARP cleavage. Conclusion: 20(S)-PPD inhibits endometrial cancer cell proliferation by inducing cell death via a caspase-mediated apoptosis pathway. Therefore, the 20(S)-PPD-like ginsenosides are endowed with ample structural information that could be utilized to develop other ginsenoside-based anticancer agents.
Keywords: 20(S)-PPD; apoptosis; athymic mice; endometrial cancer; xenograft